HUBUNGAN HIGIENE PERSONAL PEDAGANG DAN SANITASI MAKANAN DENGAN KEBERADAAN TELUR CACING SOIL TRANSMITTED HELMINTHS (STH) PADA LALAPAN PENYETA DI PUJASERA SIMPANGLIMA KOTA SEMARANG - Umi Alfiani; Sulistyani Sulistyani; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Soil Transmitted Helminths (STH) is worm wich needs soil in its life cycle to become infective form. Raw vegetables tend to be contaminated by STH egg. Factors related to personal hygiene and food sanitation could affect the food quality. This study aims to analyze the relationship between foodhandler personal hygiene and food sanitation with the existence of STH egg in the raw vegetables in Simpanglima Foodcourt, Semarang. This study was an observational analytic study which used cross sectional approach. The population of this study contained of 65 workers of penyetan stalls in Simpang lima Foodcourt, Semarang and raw vegetables of penyetan that served by the traders. The sample of this study contained of 22 foodhandlers and cabbage using purposive sampling technique. The data analysis was using univariat and bivariat (chi square) analysis. There were 12 samples of 22 samples of cabbage (54,5%) that positively contaminated by STH. The types of worm eggs found were Ascaris lumbricoides (27.3%), Trichuris trichiura (18.2%) and hookworm (9.1%). The result of this study showed that p value of handwashing practice (p=0,378), nail hygiene (p=0,195), water quality (p=1,000), washing cabbage practice (p=0,004), sell spot sanitation (p=0,231), tool sanitation (p=0,032). The conclusion of this study, there were no significant correlation between handwashing practice, nail hygiene, the use of PPE, water quality, and there were significant correlation between washing cabbage practice and tool sanitation with the existence of STH egg in the cabbage.